ARP poisoning detection and protection using client's ARP table monitoring [electronic resource] - Navid Behboodian, 1986- (2012)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2012